Pengaruh Kualitas Produk Kredit Angsuran Sistem Fidusia (KREASI) terhadap Peningkatan Jumlah Nasabah - Tiara Maharani; Tassya Siti Oktaviani; Widwi Handari Adji (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to determine whether the quality of the fiduciary system installment credit product (KREASI) can influence increasing the number of customers (case study at PT. Pegadaian Pungkur branch, Bandung city). The method of T-test and F test using SPSS 25 program and descriptive quantitative approach is the type of approach used in this research. In this study, the information taken came from observational data, supporting journals, and questionnaires distributed using Google forms with samples that had been studied from 100 respondents. The results of this study prove that product quality significantly affects the increase in the number of customers. Keywords: Product quality, KREASI, Increasing Number of Customers